Toxic and mutagenic activity of water samples from natural sources of the Enbekshikazakh district of the Almaty (Eurasian Journal of Ecology, 2020)
The current ecological situation sharply raises the question of checking water sources for mutagenic,genotoxic, and phytotoxic activity. An increase in human activity around water sources increases therisk of surface water pollution by various emissions and wastes, an increase in the concentration ofvarious pollutants in the aquatic environment can lead to mutagenic activity of this source. Since therivers Esik, Turgen, and Lake Esik, located in the Enbekshikazakh district of the Almaty region, are closeto highways, various enterprises and proximity to human activities, the risk of pollution is continuallyincreasing. As a result of physicochemical analysis of the composition of water samples, an excessof the maximum permissible concentration for manganese, lead, zinc, and cadmium was found. TheAllium-test revealed toxicity and mutagenicity of the studied water samples. The phytotoxic activitywas observed in the water of the River Esik, manifested in the inhibition of onion root growth. Cytotoxicactivity in the water of the rivers Esik, Turgen, and Lake Esik was manifested in a statistically significantdecrease (p≤0.05) in the mitotic index compared to the negative control (distilled water). A weak mutagenic activity was established in water samples from the river. Esik, Turgen and Lake Esik, manifested ina statistically significant increase in the level of chromosomal aberrations in the cells of the root meristemof onions when germinating in water from these water bodies, compared with negative control (p≤0.05).Thus, the obtained results of the study of the toxic and mutagenic potential of natural surface waters fromwater bodies located on the territory of the Enbekshikazakh district of the Almaty region indicate theircontamination with environmentally hazardous factors that pose a threat to biota and human health.Key words: natural surface waters, heavy metals, Allium test, mitotic index, chromosomalaberrations.